Formação do movimento indígena “Congresso Nacional Indígena” em San Cristóbal de Las Casas, Chiapas - Alonso, Victor Federico (2019)
The aim of this thesis focus in analyse the construction of an indigenous popular movement in the city of San Cristobal de Las Casas, state of Chiapas, Mexico, composed by the Tzeltales, Choles, Tojolabales, Lacandones, Tzotzil, Mochos e Zoques, people of the Mesoamerican civilization. Supported not only by the Jesuits and the Dominican priests of city main dioceses and the progressive’s intellectuals like anthropologists, historians and politician persecuted of the state in the 70s who has brought some new and interesting proposes for ethnography researches. The main innovation of these popular movement is its refuse for the state. The negation of the bureaucratization and corporatism contributed for the formation of the Nation Indigenous Congress (CNI) an autonomous national indigenous organization, led by its actual candidate for the presidency of the Mexico republic. An indigenous called María de Jesús Patricio Martínez, Marichuy